2019
DOI: 10.1002/jimd.12184
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of pathogenic mutations targeting Glu427 of ALDH7A1, the hot spot residue of pyridoxine‐dependent epilepsy

Abstract: Certain loss-of-function mutations in the gene encoding the lysine catabolic enzyme aldehyde dehydrogenase 7A1 (ALDH7A1) cause pyridoxinedependent epilepsy (PDE). Missense mutations of Glu427, especially Glu427Gln, account for~30% of the mutated alleles in PDE patients, and thus Glu427 has been referred to as a mutation hot spot of PDE. Glu427 is invariant in the ALDH superfamily and forms ionic hydrogen bonds with the nicotinamide ribose of the NAD + cofactor. Here we report the first crystal structures of AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The most common missense mutation in ALDH7A1 has been reported as E427G Coughlin et al (2018), occurring in 30% of PDE patients Mills et al (2006), Plecko et al (2007), Mills et al (2010, a mutational hotspot for disease. A study investigating structural changes of ALDH7A1, exhibiting mutations E427G, E427Q and E427D, demonstrated a catalytic defect and a non-natural conformation of the NAD cofactor and as a result no catalytic activity (Laciak et al, 2020). The NAD adopts a flexible conformation and lacks a defined pose for E427G and E427Q variants whereas an inactive pose is demonstrated for E427D, compromising catalysis due to lack of stabilisation and increased distance of the cofactor from active site Cys.…”
Section: Structural Perspective Of Aldehyde Dehydrogenase Related Diseasesmentioning
confidence: 99%
“…The most common missense mutation in ALDH7A1 has been reported as E427G Coughlin et al (2018), occurring in 30% of PDE patients Mills et al (2006), Plecko et al (2007), Mills et al (2010, a mutational hotspot for disease. A study investigating structural changes of ALDH7A1, exhibiting mutations E427G, E427Q and E427D, demonstrated a catalytic defect and a non-natural conformation of the NAD cofactor and as a result no catalytic activity (Laciak et al, 2020). The NAD adopts a flexible conformation and lacks a defined pose for E427G and E427Q variants whereas an inactive pose is demonstrated for E427D, compromising catalysis due to lack of stabilisation and increased distance of the cofactor from active site Cys.…”
Section: Structural Perspective Of Aldehyde Dehydrogenase Related Diseasesmentioning
confidence: 99%
“…The p.Glu427Gln variant has been referred to as a mutational hotspot of the disease ( 18 ) and the region of ALDH7A1, where this variant is located, is considered to be essential to protein folding and stability ( 19 ). In addition, other variants characterized by an amino acid change in the same position (pGlu427Gly) have been associated with the disease suggesting that a change in this position may not be tolerated ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 , 21 ] Interestingly, the substrate channels in the ALDH subfamily are very different, giving them high substrate diversity. [ 20 , 22 ] Some studies have also found a physically linked state of ALDH and ADH domains that can form biologically active higher‐order spirosome structures. [ 23 ] At present, there is no report on the structure of the SNDH subfamily, and its catalytic mechanism and the substrate‐specific structural basis are still unknown.…”
Section: Introductionmentioning
confidence: 99%